b=1
3. VTT - VTH = a b Vt
IT HITA
Attachments:
![](https://hi-static.z-dn.net/files/d77/f2977998e5a797d293ab493a0e44074c.jpg)
Answers
Answered by
1
Answer:
Step-by-step explanation:
√11 - √17 / √11 + √17
now multiply by√11-√17 on both numerator and denometor
= (√11 - √17)²/(√11)² - (√17)²
= (11+17+2√1`87)/-6
= 28/-6 + 2√187/-6
= 14/-3 + √187/-3
a = 14/-3 and b = √187/-3
YOU ARE SO BEAUTIFUL
Similar questions
Physics,
7 months ago
Math,
7 months ago
Math,
1 year ago
History,
1 year ago
Social Sciences,
1 year ago